A comparison of genomic coding sequences for feather and scale keratins: structural and evolutionary implications. - Gregg, K (1984)
DNA sequences have been obtained for embryonic chick feather and scale keratin genes. Strong homologies exist between the protein coding regions of the two gene types and between the deduced amino acid sequences of the keratin proteins. Scale keratins are larger than feather keratins and the size difference is mainly attributable to four 13-amino acid repeats between residues 77 and 128 which compose a peptide sequence rich in glycine and tyrosine. The strong similarities between the two peptide structures for feather and scale in the homologous regions suggests a similar conformation within the protein filaments. A likely consequence is that the additional repeat region of the scale protein is located externally to the core filament. Tissue-specific features of filament aggregation may be attributable to this one striking sequence difference between the constituent proteins. It is believed that the genes share a common ancestry and that feather-like keratin genes may have evolved from a scale keratin gene by a single deletion event.